Current management and screening of peripheral and coronary artery disease in people with diabetes mellitus in Europe. The PADDIA/CADDIA survey. (February 2022) - Mahe, Guillaume; Brodmann, Marianne; Capodanno, Davide; Ceriello, Antonio; Cuisset, Thomas; Delgado, Victoria; Espinola-Klein, Christine; Johnson, Thomas W.; Sprynger, Muriel; Sattar, Naveed; Schnell, Oliver; Valensi, Paul
Abstract: Aims: This survey aimed to evaluate the current management and screening of coronary artery disease and peripheral artery disease in people with type 2 diabetes mellitus (T2DM) in Europe, utilizing the 2013 ESC/EASD (European Society of Cardiology/European Association for the Study of Diabetes) guidelines as a benchmark. Methods: The PADDIA/CADDIA survey is a European medical research collaboration targeting cardiologists, vascular physicians, diabetologists and general practitioners from Austria, Belgium, France, Germany, Italy, Netherlands and United Kingdom. Results: The questionnaire was completed by sixty-three physicians, of whom 75% declared assessing the cardiovascular risk of people with T2DM mostly without using a risk score (59%). More than 90% of the panel, check HbA1c, blood pressure and low-density lipoprotein cholesterol targets in their patients with T2DM and coronary or peripheral artery disease. For 94% the presence of T2DM influence their patients' management, by optimizing blood glucose, blood pressure and low-density lipoprotein cholesterol control. Only 37% considered screening for lower extremity peripheral artery disease among their T2DM patients and 35% among those with cardiovascular disease. Conclusions: Physicians mostly follow the ESC/EASD 2013 guidelines, but when it comes to screening for additional conditions including coronary artery disease or peripheral artery disease, or intensifying the antithrombotic regimen there is need for better guidance.